War in Islamic Law and International Humanitarian Law: The Gaza Case 2023–2026 - Ezzerouali, Souad; Sungay, Mohamed Hoosain (Tuah Foundation, 2026)
Scholarship on the interaction between Islamic law and international humanitarian law (IHL) has grown considerably, yet much of it remains confined to abstract doctrinal comparison and has yet to engage seriously with how these frameworks operate in real armed conflicts shaped by religious identity. This study addresses that lacuna through a focused examination of the 2023–2026 Gaza conflict, in which legal norms, religious identity, and military practice intersect. The analysis asks how the principles of distinction and proportionality are understood within fiqh al-jihād and IHL with respect to civilian protection, and how those interpretations shape application in asymmetric conflicts involving both state and non-state actors. Employing a qualitative, comparative, and socio-legal methodology, the study advances three principal findings. First, both legal traditions affirm an obligation to protect civilians through the principles of distinction, proportionality, and humanity, although they rest on distinct normative foundations. Second, divergences in practice arise less from doctrinal conflict than from political interest and the strategic deployment of legal narrative by the parties. Third, these dynamics sustain persistent gaps in civilian protection that are often entrenched by selective legal framing and weak accountability. Based on these findings, the study proposes a “Gaza Convergence Model” as a framework for more operational engagement between the two traditions. By aligning shared principles while acknowledging irreducible differences, the model seeks to strengthen both the legitimacy and the effectiveness of civilian protection in armed conflict. More broadly, the study argues for culturally grounded legal approaches and for sustained dialogue between religious and international legal orders.